Shaman Hwui Li's The Life of Hiuen-Tsiang - Beal, Samuel, (Brill | Manohar Publishers & Distributors, 2024)
India in ancient times has encountered many foreign travelers and invaders. Shakas, Kushanas, Greeks, Persians, Huns, and Indo-Romans had conquered parts of India. Many Greek chronicle writers had written about the description of India. However, the Chinese Buddhist monks had a unique experience with India. Several Chinese travelers came to India, most of whom were Buddhist monks. One of them was Hiuen-Tsiang (c. ad 602-664), who visited India during the reign of Harshavardhana. He wrote extensive pieces of literature on Buddhism and India in Chinese and studied under various Buddhist monks in India. This book covers the biography of the Chinese Buddhist monk along with his accounts written by I-Tsing. Divided into five chapters, it covers his nativity at Chenliu, and his parentage, his stay at Kau-Chang. The book covers his interactions with the Turkic tribes at Khotan, experiences in Central Asia, and other parts of Xinjiang province. His epic visit to India has been described in a detailed manner, where he stayed at Kie-jo-kio-she, known as Kannauj, visited places associated with Buddha such as Kapilavastu, Bodh Gaya, etc., and also world famous Nalanda University. The book also covers his interactions and training under various Buddhist monks cum scholars, his visit to Ujjain and Sindh region, and his visit to Bamiyan and other sites in the Hindu Kush region. This book ends with his final years at Kauchang and his demise from the world.